'Helcococcus massiliensis' sp. nov., a new bacterial species isolated from the vaginal sample of a woman with bacterial vaginosis living in Dielmo, Senegal. (September 2018) - Fall, N.S.; Raoult, D.; Sokhna, C.; Lagier, J.C.
Abstract: We report here the isolation of a new bacterial species 'Helcococcus massiliensis' strain Marseille P4590 (CSURP4590), isolated from the vaginal sample of a woman with bacterial vaginosis.